Diversidade taxonômica e funcional da microbiota de solos do manguezal do rio Cocó (Fortaleza - CE) e seleção de cepas produtoras de enzimas com potencial para aplicação industrial - Rocha, Lidianne Leal (2012)
Mangrove forests located in large urban centers suffer from various types of human impacts. The negative consequences of these impacts are visible and well publicized for macroorganisms. However, the effects on the microbiota are only now beginning to be revealed. Moreover, such microbes may be considered as an underexplored source for production of industrial interest compounds. Thus, this study assessed the diversity and composition of Bacteria and Archaea communities in soil samples from Coco mangrove, located in the city of Fortaleza (3 °45 'S, 38 ° 29 'W) by Denaturing Gradient Gel Electrophoresis (DGGE), 16S rDNA clone libraries and pyrosequencing for metagenomics library. In addition, a survey of hydrolase-producing bacteria of industrial interest was conducted. The results showed spatial variability of the communities of Bacteria and Archaea, probably related to differences in each habitat. The phylum Proteobacteria was dominant, followed by a large proportion of unclassified bacteria. Differences were observed in the classes of Proteobacteria, and Delta, and Gammaproteobacteria dominating the habitat without vegetation (Pl), Beta and Deltaproteobacteria in Rhizophora mangle rhizosphere (P2) and Betaproteobacteria in the Avicennia shaueriana rhizosphere (P3). In addition, other representative phyla as Bacteroidetes, Chloroflexi, Actinobacteria, Verrucumicrobia, Acidobacteria, Firmicutes, Planctomycetes, Gemmatimonadetes, Nitrospirae and Cyanobacteria were found. Thermotogae, Spirochaetes, Dictyoglomi, Deferribacteres, Dinococcus-Thermus, Elusimicrobia, Fusobacteria, Chlamydiae, Lenthisphaerae, Chlorobi, Fibrobacteres and Aquificae were detected as minority groups in this mangrove. Results showed a prevalence of bacterial groups commonly associated with eutrophic environments such as Betaproteobacteria, being most common in the rhizosphere soils. The phyla Synergistetes have been registered for the first time in mangrove soils as well as the class Zetaproteobacteria. With regard to the diversity of archaea there is a predominance of members of the phylum Euryarchaeota mainly represented by methanogenic archaea, which are important for the global carbon cycle. Among the eukaryotes, a low richness of fungi, mostly belonging to the class Ascomycota was revealed, this class has been described as predominant in mangroves. It is worth noticing the presence of genes conferring resistance to antibiotics and toxic compounds, and stress response genes, which may favor the survival and establishment of microorganisms in dynamic habitats such as mangrove soils. The Coco mangrove proved to be a promising source of bacteria that produce enzymes of industrial interest, notably a single promising bacteria for lipase production, identified as Burkholderia sp., was isolated.